“THE COTTER’S SATURDAY NIGHT” BY ROBERT BURNS IN THE RUSSIAN RECEPTION OF THE 19TH CENTURY - Zhatkin, Dmitry; Futljaev, Nikita (Revista Inclusiones, 2019)
The research paper presents the history of the translational reception of the “The Cotter’s Saturday Night” poem by R. Burns in Russia in the 19th century, wherein along with a widely known, repeatedly published and reflected by researchers I.I. Kozlov’s interpretation (1829), it analyzed the readings of the Burns’ work, created by V.D. Kostomarov (1861), A.M. Fedorov (1896), attracted materials of Russian literary criticism (V.G. Belinskiy, O.I. Senkovskiy, N.A. Polevoi, P.I. Veinberg, etc.), as well as other works devoted to the Russian destiny of “The Cotter’s Saturday Night”. The research is based on fundamental works in the field of historical poetics, comparativistics, history of Russian translated fine literature, theory and history of poetic translation (Alexander N. Veselovskiy, Alexey N. Veselovskiy, V.M. Zhirmunskiy, M.P. Alexeyev, Y.D. Levin, A.V. Fedorov and others). In the process of studying the scientific problem, comparative-historical, contrastive, cultural-historical and historical-typological approaches were used, as well as methods of integrated analysis. R. Burns’ poem “The Cotter’s Saturday Night”, which appeared in the Russian language in 1829 in interpretation by I.I. Kozlov, immediately attracted attention of the leading literary critics and publicists of the epoch, i.e. N.A. Polevoi, I.V. Kireevskiy, V.G. Belinskiy, who were criticizing the “loose transversion” created by I.I. Kozlov, but noting its strong points, justified mainly by the content of the original, where such important motives as picturing the rural life of ordinary people, their endless desire to find happiness, belief in fate and in the inevitability of overcome circumstances come to the fore. In early 1860-ies, on the background of general liberalization of the public life, the appearance of V.D. Kostomarov’s translation came unexpectedly as he russified the original and emphasized the patriarchal character of people’s life and religiousness of villagers, thus contradicting the democratic vision of the life and work of the great Scottish poet, which were actively formed in the period of reforms by Alexander II.